Regular poles of local L-functions for GSp(4) with respect to split Bessel models (the subregular cases) - Rösner, Mirko; Weissauer, Rainer (Arxiv, 2018)
Piatetskii-Shapiro has defined local spinor L-factors for infinite-dimensional irreducible representations of GSp(4,k) over a local non-archimedean field k, attached to a choice of a Bessel model. We classify the so-called subregular poles, these are the regular poles that do not come from the asymptotic of the Bessel functions. For anisotropic Bessel models there are no subregular poles.